The Role and Achievments of Studentss in Faculty of Education Major in Thai Language Teaching of 5th Year on 2020 : A Case Study of Yasothon Buddhist Collage: บทบาทและความสำเร็จของนักศึกษาคณะศึกษาศาสตร์ สาขาวิชาการสอนภาษาไทยชั้นปีที่ 5 ปีการศึกษา 2563 : กรณีศึกษาวิทยาลัยศาสนศาสตร์ยโสธร - Payoko, Phamaha Jirayuth (Journal of Graduate MCU KhonKaen Campus, 2022)
This research the objectives are as follows: 1) to study the problem level of teaching professional experience training of students of the faculty of education. department of teaching thai language and mentoring teachers in educational institutions. 2) to study the guidelines for the development of teaching professional experience training of students according to the opinions of those involved in teaching professional experience training. 3) to examine the level of opinions on the guidelines for the development of professional teaching experience training from experts. and 4) to study the roles and achievements of students in teaching professional experience faculty of education department of teaching thai language and mentors in schools. This research was a mixed research using a quantitative research sample of 48 persons and a qualitative research target of 20 subjects. The results showed that Problem level in teaching professional experience training of students of the Faculty of Education Thai language teaching and mentoring in educational institutions consists of 8 issues as follows: pre-training preparation, educational quality assurance, educational measurement and evaluation, motivation, school interaction, lesson plan preparation, compensation, and the right to transfer schools and count on continuous training. Guidelines for developing the development of teacher professional experience training consist of 7 issues as follows: participation in activities, being a teacher, adapting to the current situation and lifelong learning. The level of opinions about the teaching experience of students practicing teaching experience overall, it was at a high level (μ 3.88) and factors affecting the success of students practicing teaching experience consisted of 5 aspects, namely, desirable characteristics of a teacher’s profession, self-promotion and development, teaching management in the current situation, and development of the process of teaching professional experience. and the attitude aspect of the educational institute administrators Teacher mentors and students’ professional experience training.